Developing Targeted Social Assistance in Russia: Impediments and Possibilities. Issue 5 (2nd November 2019) - Ovcharova, Lilia; Gorina, Elena
Abstract : This article assesses the potential for further developing targeted social assistance programs in Russia on the basis of need assessment. These programs are considered within the system of social assistance at the federal and regional level in terms of funding and coverage of the population. It is shown that at most a quarter of regional budget expenditures in this area could be refocused toward need assessment–based programs. The impediments to targeted social assistance programs in Russia are analyzed, and three changes that are necessary for their further development are proposed.